2019
DOI: 10.3390/ijms20122917
|View full text |Cite
|
Sign up to set email alerts
|

Jasmonic Acid-Induced VQ-Motif-Containing Protein OsVQ13 Influences the OsWRKY45 Signaling Pathway and Grain Size by Associating with OsMPK6 in Rice

Abstract: Jasmonic acid (JA) is a plant hormone that plays an important role in the defense response and stable growth of rice. In this study, we investigated the role of the JA-responsive valine-glutamine (VQ)-motif-containing protein OsVQ13 in JA signaling in rice. OsVQ13 was primarily located in the nucleus and cytoplasm. The transgenic rice plants overexpressing OsVQ13 exhibited a JA-hypersensitive phenotype and increased JA-induced resistance to Xanthomonas oryzae pv. oryzae (Xoo), which is the bacteria that causes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 63 publications
1
36
0
Order By: Relevance
“…The calcium dependent protein kinases and VQ proteins are involved in various biological processes in plants, including growth, development, and abiotic and biotic stress responses (Wang et al 2010 ; Li et al 2014 ; Jing and Lin 2015 ; Shi et al 2018 ; Zhong et al 2018 ). Moreover, two VQ proteins genes, AtVQ14 and OsVQ13 , have been found to control seed size in plant (Garcia et al 2003 ; Wang et al 2010 ; Uji et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The calcium dependent protein kinases and VQ proteins are involved in various biological processes in plants, including growth, development, and abiotic and biotic stress responses (Wang et al 2010 ; Li et al 2014 ; Jing and Lin 2015 ; Shi et al 2018 ; Zhong et al 2018 ). Moreover, two VQ proteins genes, AtVQ14 and OsVQ13 , have been found to control seed size in plant (Garcia et al 2003 ; Wang et al 2010 ; Uji et al 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…The primary structure of VQ proteins is highly diverse in regions other than the VQ motif (Jing and Lin 2015 ). Two VQ proteins, AtVQ14 and OsVQ13 were reported to control seed development in plant (Wang et al 2010 ; Uji et al 2019 ). In the present study, we found OsVQ4 was also responsible for grain size.…”
Section: Discussionmentioning
confidence: 99%
“…Sun et al examined changes in the phosphorylated proteomics of rice response to SA, suggesting that SA-mediated phosphorylation regulation may lead to different resistances of the two rice varieties [35]. OsVQ13 positively regulates JA signal by activating OsMPK6-OsWRKY45 signaling pathway in rice [36]. Jasmonic acid reduces the sensitivity of RBSDV infection by inhibiting the brassinosteroid (BR) pathway [37].…”
Section: Crosstalk Between Multiple Defensive Metabolite Response Genmentioning
confidence: 99%
“…Sun et al examined changes in the phosphorylated proteomics of rice response to SA, suggesting that SA-mediated phosphorylation regulation may lead to different resistances of the two rice varieties [34]. OsVQ13 positively regulates JA signal by activating OsMPK6-OsWRKY45 signaling pathway in rice [35]. JA reduces sensitivity of RBSDV infection by inhibiting the brassinosteroid (BR) pathway [36].…”
Section: Crosstalk Between Multiple Defensive Metabolite Response Genmentioning
confidence: 99%